ANALYSIS OF QUEUEING SYTEM AND TELLERâS SERVICE OPTIMIZATION AT THE SUB-BRANCH OFFICE OF BANK BJB FOR THE REGIONAL GOVERNMENT OF WEST BANDUNG REGENCY - Reza Kamil Risnaedi, Muhamad
The banking industry faces challenges in maintaining speed and efficiency in customer service, leading to customer dissatisfaction and reduced operational efficiency. This study focuses on the queuing system and teller service optimization at Bank BJB sub-branch office in West Bandung Regency, aiming to improve customer satisfaction and operational efficiency. The research employs a comprehensive approach, using queuing theory analysis and Root Cause Analysis techniques, particularly the Current Reality Tree, to analyze the current performance of the queuing system and teller service time. The study identifies the root causes of prolonged waiting times and service durations and develops strategies to optimize them. The research findings offer valuable insights and strategies for optimizing queuing systems and teller service times, ultimately benefiting both the bank and its customers. The implications of this study are significant, contributing to the enhancement of operational efficiency and customer satisfaction within the banking industry. The study highlights the importance of identifying and addressing the core problems contributing to adverse effects within the system. Overall, this study is a valuable contribution to the field, offering insights and strategies for optimizing queuing systems and teller service times, ultimately benefiting both the bank and its customers. This study investigates the queuing system and service efficiency at the Bank focusing on enhancing customer service operations.